PENGARUH VARIABEL-VARIABEL MONETER TERHADAP KINERJA PERBANKAN ISLAM: UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERAT - sriyono sriyono (Fakultas Ekonomi Universitas PGRI Adi Buana, 2016)
The growth and competition of Islamic banking in Indonesia is faster and tight, because of that the Islamic banks need to improve its performance in order to attract investors and clients, meanwhile monetary variables influencing on performance of banking. This study aims to determine how role of Size as a moderating variable on relantionship betwen inflation and interestrate to company performace, whether size as a moderating variable has significant effect to company perfomance. Data of research collected since 2010 to 2013 , hypothesis testing is using Moderating Regression Analysis. The result of this study showed that company size has significant and positive as moderating variable to influence performance company. Key Word : inflation, interest rate, size, performance